THE INFLUENCE OF AIRPORT QUALITY ON CUSTOMER SATISFACTION YOGYAKARTA INTERNATIONAL AIRPORT (YIA) IN KULON PROGO YOGYAKARTA - Larasati, Rian; Zulfiah, Evi; Jayamahe, Dimas (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to determine the effect of airport quality on customer satisfaction at Yogyakarta International Airport (YIA) in Kulon Progo Yogyakarta. This research uses validity tests, reliability tests, and the analysis used is multiple linear regression. Test the hypothesis using the t test, f test and R2 test. The results of this research show that the variables: Tangibles X1, Reliability X2, Responsiveness X3, Assurance In this research, the sampling technique used was non-probability sampling using purposive sampling, the number of samples in this research was 100 respondents.